2021
DOI: 10.1002/ijgo.13848
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Quechua‐speaking indigenous pregnant women from a rural community in Peru with telemonitoring during the COVID‐19 pandemic

Abstract: Synopsis Although the majority of Quechua‐speaking indigenous pregnant women are satisfied with telemonitoring during the COVID‐19 pandemic, there are still aspects to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The articles in this special edition use positive approaches. This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The articles in this special edition use positive approaches. This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
“…Twelve articles in the special issue investigate a range of topics related to pregnancy care and birth. De La Cruz‐Ramirez et al, 4 Khalil et al, 9 Jumah et al, 5 and Gould et al 13 explored how maternity care is provided and how it can better meet the needs of Indigenous women. De La Cruz‐Ramirez et al 4 found that Quechua‐speaking Indigenous women in Peru were largely satisfied with telephone support from midwives during the COVID‐19 pandemic and identified how to strengthen the program further.…”
mentioning
confidence: 99%
See 3 more Smart Citations